Dehervation of the hepatic pedicle and pyloroplasty in biliary surgery: about 73 observations. Prior communication - Badano Repetto, José L; Groisman, Mauricio (Cirugía del Uruguay, 2020)
The authors wake a remarkable stress, in · a keen and correct diagnostic in the diseases of the biliary tracts. This brings as a consequence, the rational choice of the treatment to be done. They proclaim in a special way, the denervation of the hepatic pedicle, with pyloroplasty, associated or not, to the cholecystectomy. They present a casuistical that confirms this kind of behaviour.